1982
DOI: 10.1007/bf00491470
|View full text |Cite
|
Sign up to set email alerts
|

Benzamide action at ?2-adrenoceptors modifies catecholamine-induced contraction and relaxation of circular smooth muscle from guinea-pig stomach

Abstract: Dopamine was shown to act on the circular smooth muscle of the stomach body to cause contraction at a yohimbine-sensitive site (alpha 2) and a relaxation at a prazosin-sensitive site (alpha 1). Metoclopramide and tiapride failed to modify either response, failed to antagonise a relaxation to phenylephrine at alpha 1 sites in the same tissue, and failed to modify the contractions caused by dopamine and phenylephrine at an alpha 1-adrenoceptor site in the pyloric sphincter. However, (+)- and (-)-sultopride and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…We also found no evidence for post-junctional az-adrcnoceptors, either excitatory as reported in guinea-pig gastric smooth muscle (Sahyoun et al 1982). or inhibitory as reported in the guinea-pig ileum (Bauer 1982;Bauer & Kuriyama 1982).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…We also found no evidence for post-junctional az-adrcnoceptors, either excitatory as reported in guinea-pig gastric smooth muscle (Sahyoun et al 1982). or inhibitory as reported in the guinea-pig ileum (Bauer 1982;Bauer & Kuriyama 1982).…”
Section: Discussioncontrasting
confidence: 61%
“…examine these r-adrenoccptor mediated responses in the rat gastric fundus using selective a,-and a,-adrenoceptor agonists and antagonists. As r2-adrenoceptors in the gastrointestinal tract have also been reported to be present prejunctionally on non-adrenergic, non-cholinergic nerves (Fontaine et a1 1984) and post-junctionally on smooth muscle mediating contraction (Sahyoun et al 1982) or relaxation (Bauer 1982;Bauer & Kuriyama 1982), their presence at these sites in the rat gastric fundus was also investigated. Preliminary accounts of this work have previously been reported (Dettmar et a1 1984(Dettmar et a1 , 1985a(Dettmar et a1 , b, 1986.…”
mentioning
confidence: 99%
“…42,43 The same experiments also revealed that higher concentrations of dopamine induced relaxation mediated by α 1 -adrenoreceptors. 42,43 In an in vitro study 45 involving horses, an α 2 -agonist (UK 14304-18) caused a significant increase in contraction amplitude, contraction frequency, and tone in jejunal longitudinal muscle strips but had no effect on jejunal circular muscle strips. Therefore, it is possible that the response to dopamine observed in longitudinal muscle strips of equine jejunum is partially mediated by action on α 2adrenoreceptors.…”
Section: Discussionmentioning
confidence: 75%
“…[39][40][41] However, in circular muscle strips from guinea pig stomachs, dopamine increases contractile activity at concentrations equivalent to those used in the present study (10 -7 to 10 -5 M). [42][43][44] The mechanism for the increased contractile activity induced by dopamine operates via α 2adrenoreceptors, given that yohimbine shifts the concentration response curve to the right. 42,43 The same experiments also revealed that higher concentrations of dopamine induced relaxation mediated by α 1 -adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation